1988
DOI: 10.1002/ar.1092200205
|View full text |Cite
|
Sign up to set email alerts
|

Removal of collagen bundles in murine uterus during postpartum involution

Abstract: The localization of collagenolytic activity within the tissue compartments of the mouse uterus was investigated during postpartum involution. The rate of collagenase activity was measured by analysis of tissue levels of hydroxyproline from the day of parturition to the 10th postpartum day. Collagen bonding was analyzed by viewing birefringence induced by the picrosirius red-binding technique. An attempt was made to interrelate quantitative analysis with the histologic distribution of collagen during postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…The present study has shown that most of the collagen type III is removed from the endometrial stroma by day 10 postpartum, although this is not the case for the longitudinal smooth muscle. These findings agree with a previous report that collagen degradation occurs primarily in the endometrium (Shimizu & Hokano 1988). Removal of collagen type III from the endometrial stroma and from the endothelium of blood vessels, and also removal of collagen type III from the bundles and from the connective tissue band underlying the longitudinal smooth muscle layer, may contribute to the rapid decrease in uterine collagen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study has shown that most of the collagen type III is removed from the endometrial stroma by day 10 postpartum, although this is not the case for the longitudinal smooth muscle. These findings agree with a previous report that collagen degradation occurs primarily in the endometrium (Shimizu & Hokano 1988). Removal of collagen type III from the endometrial stroma and from the endothelium of blood vessels, and also removal of collagen type III from the bundles and from the connective tissue band underlying the longitudinal smooth muscle layer, may contribute to the rapid decrease in uterine collagen.…”
Section: Discussionsupporting
confidence: 93%
“…Collagen contains all of the hydroxyproline in the body; the amount of hydroxyproline in an organ can be taken as a measure of its collagen content (Bloom & Fawcett 1975; Dawson & Milne 1978). The removal of collagen from the uterus during postpartum involution has been studied in rats (Harkness & Moralee 1956) and in mice (Shimizu & Hokano 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the total uterine collagen mass increases up to 20-fold during pregnancy, and after parturition the uterus rapidly recovers to prepregnant size. This postpartum involution is accomplished within the first two days after giving birth and involves transcriptional activation of the collagenase gene and increased release of collagenase extracellularly followed by the massive degradation of most of the collagen deposited in the uterus within a few days (44,45). In mutant females, degradation of collagen was severely disturbed, leading to the accumulation of nodules in the uterine wall.…”
Section: Tissue Remodeling In the Adult Depends On A Functional Collamentioning
confidence: 99%